Analysis of the Influence of Education, Health, and Gross Regional Domestic Product (GRDP) on Poverty in Central Maluku Regency - Lutfy Isnaeni Tuharea; Muhammad Bugis; Maria Katje Tupamahu (PT Mattawang Mediatama Solution, 2024)
This thesis aims to analyze the influence of education, health, and Gross Regional Domestic Product (GRDP) on the poverty level in Central Maluku Regency, both partially and simultaneously related to the Social Welfare Program. The research employs a conceptual framework consisting of three main dimensions: education, health, and GRDP. Through quantitative and qualitative approaches, the impact of education on poverty is elaborated, the role of health in reducing the poverty rate is investigated, and the relationship between GRDP and poverty levels is explored in depth. The research methods used include primary and secondary data collection, statistical analysis, and interviews with local stakeholders. The research results are expected to provide a holistic insight into the factors contributing to poverty in Central Maluku Regency. The results of this study illustrate that education, health, and GRDP variables partially influence poverty in Central Maluku Regency. This can be seen from the probability values of each variable, which are less than 0.01 %. This research is expected to provide conceptual and practical contributions to poverty alleviation efforts at the local level. Policy implications are expected to guide strategic steps to improve education, health, and economic growth to reduce poverty levels in this region. In conclusion, this thesis contributes to a better understanding of the complexity of poverty issues in Central Maluku Regency and provides a basis for the development of more effective intervention strategies to address these challenges.